Latitudinal Variations of Daytime Periodic Ionospheric Disturbances From Beidou GEO TEC Observations Over China. Issue 3 (1st March 2021) - Hu, Lianhuan; Lei, Jiuhou; Sun, Wenjie; Zhao, Xiukuan; Wu, Baoyuan; Xie, Haiyong; Yang, Sipeng; Wu, Zhi; Zheng, Jianchang; Ning, Baiqi; Ding, Feng; Li, Guozhu
Abstract: Using total electron content (TEC) data from a chain of Beidou geostationary satellite TEC receivers along ∼110°E during 2016–2019, the local time, seasonal, and latitudinal occurrence characteristics of periodic TEC perturbation associated with medium scale traveling ionospheric disturbances (MSTIDs) are investigated. The results show that the daytime periodic ionospheric disturbances appear prominently in winter with dominant periods ∼30–40 min. An interesting feature is that the latitudinal variations of periodic ionospheric disturbances show two occurrence peaks at higher and lower latitudes, with a minimum centering around 30°N‐33°N, where almost no periodic ionospheric disturbance was detected under the threshold of absolute TEC perturbation greater than 0.3 TECU. Further, using two short‐baseline GNSS receiver arrays at middle and low latitudes, the propagation characteristics of the periodic ionospheric disturbances were derived. The median values of propagation azimuth, phase velocity, and period of the ionospheric disturbances at middle (low) latitude are 153.1° (157.4°), 36.7 min (33 min), and 97.2 m/s (62.5 m/s), respectively, showing typical characteristics of MSTIDs. We surmise that the perturbation source and background electron density could play important roles in causing the latitudinal variation of daytime periodic ionospheric disturbances along 110°E. Key Points: A statistical analysis of daytime periodic ionospheric disturbance occurrence at middle and low latitudes along ∼110°E is performed The occurrence of daytime periodic ionospheric disturbances shows two peaks at higher and lower latitudes, with a minimum centering ∼30°N‐33°N The latitudinal dependence of ionospheric disturbances is suggested to be linked with perturbation source and background electron density